Perioperative Animal Care for Xenotransplantation from Genetically Edited Pigs to Monkeys - ZHU Chan; ZHANG Dongliang; ZHAO Deli; SHI Xueqin; QIAN Lei; ZHANG Xuan; JIN Yan; DUAN Wei; QI Ruocheng; LIU Chaohua; YANG Xuekang; HAN Juntao; et al. (Shiyan dongwu yu bijiao yixue)
Objective To discuss the perioperative care and wound protection of xenotransplantation from genetically edited pigs to monkeys, with the goal of improving the success rate of such experimental procedures. Methods From October 2022 to October 2023, perioperative care and wound protection were performed on 7 recipient rhesus monkeys undergoing xenotransplantation of genetically edited pig tissues and organs. Customized wound protective garments were designed based on monkeys' size and surgical area to protect the wounds, alongside meticulous perioperative care. This included preoperative preparation and medication, intraoperative monitoring of physiological indicators and anesthesia management, and postoperative care comprising wound protection, observation and monitoring, and nutritional support. Results All seven monkeys successfully underwent xenotransplantation. With the aid of protective garments and detailed care, all surgical wounds healed by first intention, and postoperative recovery was satisfactory. Conclusion Proper care and wound protection during xenotransplantation from genetically edited pigs to monkeys not only promote wound healing, but also alleviate pain and harm to animals. This has significant implications for advancing experimental research in pig-monkey xenotransplantation and enhancing animal welfare.